Pengaruh Konsumsi Minuman Isotonik terhadap Daya Tahan Otot Saat Melakukan Latihan Beban - Manggala, Janan; Lintong, Fransiska; Franky Rumampuk, Jimmy (Green Publisher Indonesia, 2025)
Weight training have become a sports of choice among people to improve physical fitness and strength. Muscle endurance is named as one of the factors that may effect weight training performance and fitness development. Isotonic drinks were formulated to have similar osmolality as the fluids in human body (275-330 mOsm/L) to help the nutrients to be absorbed in a small amount of time. Isotonik drinks may potentially improve muscle endurance with its carbohydrates and electrolytes content to replace the energy and electrolytes loss during intense weight training. This study aim to understand the effect of isotonic drinks consumption on muscle endurance during weight training. This was an experimental study using pre-test and post-test with control group design to analyze the difference of muscle endurance before and after isotonic drinks consumption during weight training. The data was analyzed using t-paired test. The result showed that there is a significant improvement in muscle endurance numbers upon group that was given isotonic drinks with value of significancy < 0,001 (p < 0,05). This study concludes that there there is an effect of isotonic drinks consumption on muscle endurance during weight training.